Collins COBUILD Advanced Learner's English Dictionary (Glasgow HarperCollins Publishers, 2006)
This edition of the Collins COBUILD Advanced Learner's English Dictionary offers up-to-date coverage of today's English in a clear, attractive format.
Include Figures and Color Illustrations.
Keywords: English language -- English language--Usage -- Electronic dictionaries